Clinical significance of hyperuricaemia in biopsy-proven diabetic kidney disease ━ a single-centre retrospective study - Yu, Jin; Tu, Xiao; Xu, Kunyue; Tang, Xuanli; Wu, Yufan; Jiang, Xue (Frontiers in Endocrinology, 2025)
AimsHyperuricaemia is associated with the development of Diabetic kidney disease (DKD). However, the mechanism of hyperuricaemia causing the progression of DKD remain unclear.MethodsThis is a single-centre retrospective study. 155 biopsy-proven DKD patients were grouped into hyperuricaemia and non-hyperuricaemia groups. Kaplan-Meier analysis and landmark curves were performed to explore predictors of end-stage renal disease (ESRD), Cox regression analysis was used to screen for factors, a nomogram was constructed to predict the renal prognosis of DKD.ResultsPatients in hyperuricaemia group had higher serum creatinine (Scr), degree of mesangial expansion and IFTA score and lower GFR, haemoglobin. SUA level was positively correlated with IFTA scores. The Kaplan-Meier curve and landmark analysis revealed worse survival in hyperuricaemia group, especially after 12 months. 11 variables, including age, sex, haemoglobin, Scr, SUA, and pathological score were collected to make a nomogram model. In the testing and training sets, the AUCs at 1, 3, and 5 years were 0.888, 0.939, and 0.886 and 0.947, 0.867, and 0.905, respectively.ConclusionThe clinicopathologic manifestation of DKD patients with hyperuricaemia was much more severe, and hyperuricaemia predicted a worse renal prognosis. A new renal prognosis prediction model including SUA was constructed for DKD with higher accuracy.